ANALISIS KONTEN INSTAGRAM PADA BRAND PAKAIAN DALAM SCULPT - Jessica Julia Markus; Naila Rushad (LPSDI Bina Patria, 2025)
The current internet era makes it easy for the fashion industry to promote products, create trends, and communicate with their agents. The function of social media is one of the strategies in digital marketing that requires companies to create interesting content. Instagram plays a role in the Sculpt brand's internet communication strategy with lifestyle and aesthetic photos and videos for the audience. The main consumers in Indonesia, especially Generation Z and the Millennial Generation, in the fashion world are not only consumers but also content creators. They establish brands with fast fashion trends and only look for buyers who use Instagram. The New Media Theory proposed by Pierre Levy, for the development of his account @sculpt.id on Instagram. The content posted on the Instagram account aims to introduce products and attract customers' attention so that they remember Sculpt Shapewear products more. To achieve this, social media is used effectively to promote products.